2011
DOI: 10.1016/j.synthmet.2010.11.044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deuteration on organic magnetoresistance

Abstract: Measurements of the effect of a magnetic field on the light output and current through an organic light emitting diode made with deuterated aluminium tris (8-hydroxyquinoline) have shown that hyperfine coupling with protons is not the cause of the intrinsic organic magnetoresistance. We suggest that interactions with unpaired electrons in the device may be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The superior MR response of the D-Alq 3 OSV is maintained at various voltages (Fig. 2c) This observation is at variance with an earlier study in which much smaller dependence on the isotope exchange was reported 9,14 . Second, the MEL(B) response shows another feature at low fields (B<~2 mT) [ Fig.…”
Section: B Magneto-resistance In Organic Spin-valvessupporting
confidence: 48%
See 1 more Smart Citation
“…The superior MR response of the D-Alq 3 OSV is maintained at various voltages (Fig. 2c) This observation is at variance with an earlier study in which much smaller dependence on the isotope exchange was reported 9,14 . Second, the MEL(B) response shows another feature at low fields (B<~2 mT) [ Fig.…”
Section: B Magneto-resistance In Organic Spin-valvessupporting
confidence: 48%
“…This should occur since the HFI constant, a HF , scales with the nuclear g-factor 13 , whereas the other proposed interactions are mostly isotope insensitive. Consequently, the isotope exchange effect on the MFE(B) response in Alq 3 -based OLED was recently studied to scrutinize the proposed spin-mixing models 9,14 . It was concluded that the MFE in Alq 3 -based OLED is not dominated by PP or BP species, since it was found that the HFI does not play a major role in determining the MC(B) and MEL(B) responses.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario is supported by the observation of phosphorescence in Alq 3 films [95]. It is worth noting that the MC in fullerene-based OLEDs was not observable due to ) (blue lines) [65], and triple Lorentzian function (olive line) [91]. Reproduced with permission.…”
Section: Advances In Experimental Parts Of Magnetic Field Effect In Omentioning
confidence: 62%
“…This scenario was discussed before by Wang et al [60] Gillin et al found that OMAR can be better fit by the sum of two or three Lorentzian functions (see the olive line in Fig. 6) [90,91]. This suggests that there may be more than one OMAR mechanism involved in the effect depending on OSC materials, device fabrication and operating condition [60,90].…”
Section: Advances In Experimental Parts Of Magnetic Field Effect In Omentioning
confidence: 63%
“…These are known as the low-field effect and the high-field effect. The low-field effect has been ascribed to the spin evolution of the PP excitations in the local hyperfine field before exciton formation. This effect saturates at a field higher than the hyperfine field region, which is typically about 4 mT. However, in some cases, a further positive process is found, which does not saturate at high fields; and this is due to the field effect on the triplet excitons after the PP T → triplet exciton formation. , In particular, Chen et al reported an additional decay in the MEL­( B ) response at the high-field region and low temperatures in Alq 3 -based OLEDs .…”
Section: Introductionmentioning
confidence: 99%